Guest Editor’s Note - Mokhtar, Aida (Intellectual discourse, 2019)
This Special Issue of Intellectual Discourse contains seven articleson the theme of disability studies. The goal of the Special Issue isto create awareness of research studies on the area of disability.The inclusion of persons with disabilities in various areas such aseducation, healthcare, access to buildings and information meets theUnited Nations Sustainable Development Goals (SDGs) which arefundamental to the focus of the articles. The scope of the theme is wideas it encompasses several perspectives namely the extra costs of havinga disability, advertisements and their depiction of inclusion and personswith disabilities, the inclusiveness of Malaysian urban cities, parentingchildren with hearing impairment, an examination of stress in parents ofchildren with autism, the costs of different types of caregivers and thedesign of a speech delay screening mobile application for Malaysianparents.